Herbal remedies as alternative to conventional therapies for the treatment of pediatric infectious diseases - Salehi, Bahare; Heravi, Reza Entezari; Eydian, Zahra; Stojanovic-Radic, Zorica; Martorell, Miquel; Iriti, Marcello; Sharifi-Rad, Javad (Cellular and Molecular Biology, 2020)
Pediatric infections still represent a leading cause of mortality in many developing countries. Since ancient times, traditional healing systems provided some herbal remedies to treat pediatric diseases, only in some cases validated by an evidence-based approach. Therefore, this review covers the herbal remedies in Iranian traditional medicine and aims to assess the potential of phytotherapeutics as safe and effective alternatives to conventional therapies for the treatment of pediatric infectious diseases. Notably, pediatric patients may also benefit from adjuvant therapy, i.e., combined treatment with herbal remedies and conventional therapies, to improve the efficacy of conventional drugs, decrease their adverse effects at the cell-tissue-organ-organism level and reduce the occurrence of microbial strains resistant to antibiotics. Therefore, traditional healing systems still represent an unlimited source of active ingredients to be tested in preclinical assays as well as in humans in terms of efficacy and safety.